2023
DOI: 10.3389/fcimb.2023.1327069
|View full text |Cite
|
Sign up to set email alerts
|

A growing battlefield in the war against biofilm-induced antimicrobial resistance: insights from reviews on antibiotic resistance

Liu Pai,
Sandip Patil,
Sixi Liu
et al.

Abstract: Biofilms are a common survival strategy employed by bacteria in healthcare settings, which enhances their resistance to antimicrobial and biocidal agents making infections difficult to treat. Mechanisms of biofilm-induced antimicrobial resistance involve reduced penetration of antimicrobial agents, increased expression of efflux pumps, altered microbial physiology, and genetic changes in the bacterial population. Factors contributing to the formation of biofilms include nutrient availability, temperature, pH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 124 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…The las system positively regulates the expression of both rhlR and rhlI. Thus, lasI/R controls the first wave of quorum-sensing–controlled gene expression followed by rhlI/R in a synchronized arrangement system [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The las system positively regulates the expression of both rhlR and rhlI. Thus, lasI/R controls the first wave of quorum-sensing–controlled gene expression followed by rhlI/R in a synchronized arrangement system [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, when formed on inert surfaces (such as catheters and surgical prostheses) or living substrates (such as tissues of higher organisms), these structures protect bacteria from host immune responses and antibiotic treatment. Therefore, biofilm‐associated infections can have a serious impact on health, making the diagnosis and treatment of biofilms challenging (Pai et al, 2023 ). One of the most promising therapeutic alternatives to antibiotics for treating these forms of bacterial resistance is bacteriophage‐based therapy (Usman et al, 2023 ).…”
Section: Bacteriophage‐based Therapies To Combat Forms Of Resistance ...mentioning
confidence: 99%
“…The Infectious Disease Society of America proposes Dapto for use in the therapy of enterococcal and staphylococcal infections of prosthetic joints [ 11 ]. Another advantage of Dapto concerning the treatment of MDIs is its known high anti-biofilm activity [ 12 , 13 , 14 ]. In one case, it has been reported that Dapto rapidly penetrates a Staphylococcus epidermidis biofilm [ 15 ].…”
Section: Introductionmentioning
confidence: 99%